NETNOGRAPHIC STUDY OF THE MESSAGE OF SELF-ACCEPTANCE IN THE SONG "TUTUR BATIN" AMONG FEMALE LISTENERS - Shintya Margaretha Marpaung; Anis Endang SM; Indria Indria (Jurnal Scientia, 2023)
This research was conducted to see how the netnographic study of the message of self-acceptance spread in the form of a song on YouTube with the title "Tutur Batin" by Yura Yunita among female listeners. This study uses a qualitative research method which aims to explain a phenomenon in detail and answer the problems taken by the researcher. This study uses a qualitative research method with a netnographic research approach, known as ethnography on the internet by looking at its interactivity and the behavior of people from various cultures and communities in cyberspace. Netnography is a way of conducting anthropological research via the internet, using publicly available information that everyone is free to share via social media. In conducting research, researchers used non-participant observation techniques because researchers did not participate in research life, researchers only observed the comments column in the Music Video on 'Tutur Batin' song by Yura Yunita's YouTube and Library Study Techniques. The study’s results showed that female listeners' self-acceptance after listening to that song was being able to assess oneself and correct personal weaknesses, being confident and loving oneself, being independent and opinionated, being honest with oneself and using one's abilities wisely and effectively.